KINERJA PENGAWASAN INTERNAL TERHADAP INSTANSI PERANGKAT DAERAH PROVINSI KALIMANTAN TENGAH - Nofriandy Imanuel (Journal Ilmu Sosial, Politik dan Pemerintahan, 2018)
This research aims to determine the performance of internal supervision Inspectorate of Central Kalimantan Province. Indicators used in measuring internal supervision performance of the Central Kalimantan Provincial Device Institution namely Input (inputs), Process (process), Output (Output), Outcomes, Benefits, Impacts.This research was conducted by using qualitative descriptive method by interviewing Central Kalimantan provincial inspectorate staff. The data obtained is then processed by reduction steps, presenting the data and drawing conclusions. The informants interviewed in the Inspectorate of Central Kalimantan Province are 4 informants and 3 informants from different SOPD, with the number of informants 7 people.The results of this study explain that the performance of Inspectorate of Central Kalimantan Province in carrying out the function of guidance and supervision has been done well, based on the rules and applicable law. Internal supervision is done so that no abuse in government, coaching and supervision in PP 60 year 2008 is a preventive action. The factors that affect the performance of internal supervision of the regional apparatus of Central Kalimantan Province are: Supporting Factors: a. Ability b. Motivation c. Communication. Inhibiting Factor is the ability of human resources that limited the number of personnel of the supervisory apparatus, limited availability of budget, limited function of supervision activities in terms of performing the task of the absence of search function, seizure if SOPD is not open.Conducting internal control over the local apparatus institutions, the financial management is running well and neatly, reducing the administrative errors of the office, the work environment is orderly and effective, the regional apparatus institutions feel helped by the supervision and guidance by the Inpektorat of Central Kalimantan Province.For that through this thesis the authors provide suggestions that is expected for the Government to be able to overcome obstacles in implementing coaching and supervision, such as human resources limited personnel supervisory personnel, limited availability of budget.